United Kingdom : Financial Sector Assessment Program-Some Forward Looking Cross-Sectoral Issues. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The United Kingdom faces significant money laundering threats from foreign criminal proceeds, owing to its status as a global financial center, but the authorities have a strong understanding of these risks. The authorities estimated the realistic possibility of hundreds of billions of pounds of illicit proceeds being laundered in their jurisdiction. The money laundering risks facing the United Kingdom include illicit proceeds from foreign crimes such as transnational organized crime, overseas corruption, and tax crimes. Financial services, trust, and company service providers (TCSPs), accountancy and legal sectors are high-risk for money laundering, with also significant emerging risks coming from cryptoassets. Some Crown Dependencies (CDs) and British Overseas Territories (BOTs) have featured in U.K. money laundering investigations. Brexit and COVID pandemic have an impact upon the money laundering risks in the United Kingdom. The authorities nevertheless have demonstrated a deep and robust experience in assessing and understanding their ML/TF risks. Leveraging technology tools such as big data and machine learning to analyze cross-border payments may add further dimension to their risk assessments. This technical note (TN) will focus on key aspects of the United Kingdom's anti-money laundering and countering the financing of terrorism (AML/CFT) regime: risk-based AML/CFT supervision, entity transparency and international cooperation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy